The SAMR model for the development of learning device innovations in the subject of applying electronic circuits - Rykha Avadian Wahyudi; Ibut Priono Leksono; Ujang Rohman (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
Abstrak: Pengembangan dan penelitian ini menghasilkan perangkatapembelajaran dengan model SAMR (substitution, augmentation, modification, redefinition) untuk mengintegasikanateknologi agar pembelajaranalebih inovatif danakreatif serta meningkatkan pemahaman siswa. Prosedur pengembangan perangkat pembelajaran menggunakan metode pengembangan research and development (R&D) dan pendekatan model SAMR. Teknik pengumpulanadata dilakukan dengan observasiadan angket. Tahap pengujianakelayakan dilakukanaoleh ahli media, ahli desain, ahli materi, temanasejawat dan siswa. Hasil penilaian kelayakan ahli desain diperoleh prosentase 95,5 (valid). Ahli materiadiperoleh prosentase 93,8 (valid). Ahli media diperoleh prosentase 83,8 (valid). Uji kepraktisan oleh teman sejawat diperoleh prosentase 91,7 (baik). Hasil respon terhadap produk di kelompok kecil diperoleh prosentase 98,9 (baik) dan uji coba kelompok besar diperoleh prosentasea97,5 (baik). Hasil data dan analisis penelitian, disimpulkan bahwa pengembangan perangkat pembelajaran penerapan rangkaian elektronika dengan model SAMR kelas XI memudahkan siswa dan guru berkolaborasi mencapai tujuan pembelajaran dan mengembangkan kreatifitas dan inovasi siswa dengan mengintegrasikan teknologi serta dapat diterapkan dalam pembelajaran lainnya. Abstract: By incorporating technology, this Research and Development creates learning aids that use the SAMR (substitution, augmentation, modification, redefinition) model to make learning more original and creative while improving student's knowledge. The SAMR model approach and the Research and Development (R&D) method were used in the process of creating learning tools. Questionnaires and observation were used as data-collecting tools. Media specialists, design experts, material experts, coworkers, and students participated in the feasibility testing stage. A percentage of 95.5 (valid) was attained in the design expert feasibility evaluation results. Experts in material score 93.8 (valid). A valid percentage of 83.8 was given by media professionals. Colleagues' practicality test scored 91.7 out of 100, which is good. The results of the response to the product in the small group obtained a percentage of 98.9 (good), and in large group trials, it was 97.5 (good). The results of the research data and analysis concluded that the development of learning tools applying electronic circuits using the class XI SAMR model makes it easier for students and teachers to collaborate in achieving learning goals and develops student creativity and innovation by integrating technology and can be applied in other learning.